Optic replacement in a novel modular intraocular lens system. (7th July 2016) - Guan, Jia J; Kramer, Gregory D; MacLean, Kyle; Farukhi, Aabid; Li, He; Reiter, Nicholas E; Werner, Liliana; Mamalis, Nick
Abstract: Purpose: The purpose of the study is to evaluate the stability and ease of replacement of a new modular intraocular lens (IOL) system consisting of a hydrophobic acrylic base unit and a hydrophobic acrylic optic in the rabbit model. Methods: Five New Zealand white rabbits were utilized. Bilateral phacoemulsification was performed; one eye received the test IOL (ClarVista Harmoni Modular IOL System) and the other, a commercially available hydrophobic acrylic control IOL (Alcon AcrySof SA60AT). Slit‐lamp examinations were performed weekly during postoperative weeks 1 to 6. IOL replacement procedures were performed at weeks 2 and 6 using standard instruments. The rabbits were sacrificed at the end of the study (week 6), with all globes analyzed grossly using the Miyake‐Apple technique and sectioned and processed for histopathologic examination. Results: The base component and the optic of the Harmoni IOL system remained stable and centred throughout the clinical follow up. Disengagement of the optic component from the base and replacement of the optic were safely and easily accomplished at 2 and 6 weeks postoperatively. Explantation of the control lens required posterior synechiolysis and capsular bag manipulation due to the position of the loops at the periphery of the bag, thus causing zonular stress. Conclusions: Replacement of the Harmoni optic was found to be safe and efficient compared with the control IOL, as manipulation of the capsular bag to remove haptic components is not necessary with the modular design. The base component of the modular system remained stable and centred throughout the study.